Transcutaneous Electrical Nerve Stimulation (TENS) for Primary Dysmenorrhea: An Overview - Elboim-Gabyzon M; Kalichman L (Dove Medical Press, 2020)
Michal Elboim-Gabyzon,1 Leonid Kalichman2 1Physical Therapy Department, Faculty of Social Welfare and Health Sciences, University of Haifa, Haifa 22421, Israel; 2Department of Physical Therapy, Recanati School for Community Health Professions, Faculty of Health Sciences, Ben-Gurion University of the Negev, Beer Sheva, IsraelCorrespondence: Michal Elboim-GabyzonPhysical Therapy Department, Faculty of Social Welfare and Health Sciences, University of Haifa, Balfour 9 Nahariya, Haifa 22421, IsraelTel +972-545968943Email michal.elboim@gmail.comAbstract: Primary dysmenorrhea is a chronic health condition that affects primarily young women. Transcutaneous electrical nerve stimulation (TENS) has been suggested as an effective pain reduction modality in primary dysmenorrhea. TENS is a noninvasive, inexpensive, portable method with minimal risks and a few contraindications. When necessary, it can be self-administered on a daily basis during everyday activities. Several studies have investigated the effectiveness of TENS in reducing pain, decreasing the use of analgesics, and improving the quality of life in primary dysmenorrhea patients. These studies have some limitations in methodological quality and therapeutic validation. However, the overall positive effects of TENS in primary dysmenorrhea encountered in all prior studies indicated its potential value. This review presents the clinical recommendations for TENS parameters for treating primary dysmenorrhea symptoms based on previously published studies.Keywords: primary dysmenorrhea, transcutaneous electrical nerve stimulation, TENS, pain, life quality, treatment